Determination of Level of Food Additives in Labisia pumila (LP) Beverages Consumed in Kuantan, Malaysia - Ade Chandra Iwansyah; Masithah Mohammad Yusoff; Faridah Kormin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
The content levels of several food additives (gallic acid, benzoic acid and caffeine) in commercial Labisia pumila (LP) beverage samples in Kuantan, Malaysia were determined by high performances liquid chromatography (HPLC). These analytical measurements were undertaken primarily to assess the compliance of content levels of the investigated food additives and their daily intake doses with permissible levels. The results obtained from this study indicated that the average levels of GA, caffeine and benzoic acid in the analyzed beverages were 37.62-229.35 ppm, 43.46 -168.00 ppm and 98.10-241.13 ppm, respectively. In addition, the concentrations of these food additives have been converted into daily intake doses based on beverage consumption. It was estimated that the mean daily intake of GA, caffeine and benzoic acid by the adult population of Kuantan through the consumption of the analyzed beverages were 0.39 mg/kg body weight/day for GA, 0.59 mg/kg body weight/day for caffeine (19.6 % ADI) and 0.43 mg/kg body weight/day for benzoic acid (8.6%ADI). None of the analyzed beverage sample was found to violate the current legal limits as stipulated in Malaysian food regulation.